Synthesis and Characterization of Mn2+, Fe2+, Co2+ and Ni2+, Complexes of Schiff base derived from Phenylene Diamines and 3-Carboxaldehyde - Kumar, M.; Kumar Sinha, Arabinda (Asian Journal of Chemistry, 2010)
Schiff bases synthesized by the reaction of pyridine-3-carboxaldehyde with o-phenylene diamine (COPDE) and m-phenylene diamine (CMPDE) form monomeric and dimeric complexes with divalent Mn2+, Fe2+, Co2+ and Ni2+ ions. Square planar geometry has been assigned to [M(L)2]Cl2 complexes; whereas M2(L)4Cl2, M2(L)4(NO3)2 [(ML2·2H2O)]SO4 and ML2(CH3COO)2 complexes are octahedral (M = Mn2+, Fe2+, Co2+ and Ni2+; L = COPDE or CMPDE). Structures of complexes have been assigned on the basis of elemental analysis, molar conductance, molecular weight determination, IR, UV and magnetic moment values data.